Relationship between the Boyanov–Naydenov problem and Kolmogorov-type inequalities - Kofanov, V. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5We prove that the Boyanov–Naidenov problem $\|x^{(k)}\|_{q,\, \delta} \to \sup,$ $k= 0,1, \ldots ,r-1,$ on the classes of functions $\Omega^r_p(A_0, A_r) := \{x\in L^r_{\infty}\colon \|x^{(r)}\|_{\infty}\le A_r,\ L(x)_p\le A_0 \},$ where $q \ge 1$ for $k\ge 1$ and $q \ge p$ for $k=0,$ is equivalent to the problem of finding the sharp constant $C = C(\lambda)$ in the Kolmogorov-type inequality \begin{gather}\|x^{(k)}\|_{q,\, \delta} \leq C L(x)_{p}^{\alpha} \big\|x^{(r)}\big\|_\infty^{1-\alpha}, \quad x\in \Omega^{r}_{p, \lambda}, \tag{1}\end{gather} where $\alpha=\dfrac{r-k+1/q}{r+1/p},$ $\|x\|_{p,\, \delta}:=\sup \{\|x\|_{L_p[a,\, b]}\!\colon  a, b \in {\rm \bf R},\ 0< b-a \le \delta \},$ $\delta > 0,$ $\Omega^{\,r}_{p, \lambda}:= \bigcup \{\Omega^{\,r}_p(A_0, A_r)\colon A_0 = A_r L(\varphi_{\lambda, r})_p \},$ $\lambda > 0,$ $\varphi_{\lambda, r}$ is a contraction of the ideal Euler spline of order $r,$ and $L(x)_p:=\sup\big\{ \|x\|_{L_p[a,\, b]}\colon a, b \in {\rm \bf R},\ |x(t)|>0,\ t\in (a, b)\big\}.$In particular, we obtain a sharp inequality of the form (1) on the classes  $\Omega^{\,r}_{p, \lambda},$ $\lambda > 0.$ We also prove the theorems on relationships for the Boyanov–Naidenov problems on the spaces of trigonometric polynomials and splines and establish the relevant sharp Bernstein-type inequalities.